1976
DOI: 10.1136/jnnp.39.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cerebral metabolism after bilateral carotid artery ligation in normotensive and spontaneously hypertensive rats.

Abstract: SYNOPSIS Mortality and cerebral glycolytic metabolism were studied after bilateral ligation of the common carotid artery in normotensive Wistar rats (NTR), and spontaneously hypertensive rats (SHR) derived from Wistar strain. In the first 24 hours after occlusion of carotid arteries, 72% of 108 SHR died, whereas it was fatal in only 1600 of 43 NTR. In SHR, cerebral lactate and cerebral lactate/pyruvate ratio (L/P ratio) increased by 12.4 and 12.1 times the control, respectively at five to six hours after ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

1976
1976
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…5,6 throughout the experiment. Our previous studies [7][8][9][10] have demonstrated that The animals were divided into two experimental spontaneously hypertensive rats (SHR) are more sus groups: one for measurements of local CBF and the ceptible to cerebral ischemia than normotensive rats other for determinations of brain tissue metabolites. (NTR) following bilateral carotid occlusion, suggest ing that the cerebral vasoreactivities to changes of the…”
mentioning
confidence: 99%
“…5,6 throughout the experiment. Our previous studies [7][8][9][10] have demonstrated that The animals were divided into two experimental spontaneously hypertensive rats (SHR) are more sus groups: one for measurements of local CBF and the ceptible to cerebral ischemia than normotensive rats other for determinations of brain tissue metabolites. (NTR) following bilateral carotid occlusion, suggest ing that the cerebral vasoreactivities to changes of the…”
mentioning
confidence: 99%
“…1 This susceptibility is not unique to the gerbil,' since 100 percent mortality rates have been reported for other laboratory rodents subjected to bilateral carotid arterial ligation. 10 ' n It was the gerbil's special susceptibility to unilateral carotid arterial ligation, however, which led to its introduction as a useful model of cerebral ischemia. 1 '' When one carotid artery is ligated, the ipsilateral cerebral hemisphere is dependent upon the anterior communicating artery for the critical blood supply which would prevent infarction and allow the animal to survive.…”
mentioning
confidence: 99%
“…However, SHRs subjected to the bilateral CCA occlusion (SHR-2VO) have shown greater CBF reduction accompanied by more extensive cerebral infarcts and demyelinating changes and higher mortality rate (72%; 78 of 108) than the normotensive counterpart WKY rats (16%; 7 of 43). 14,15 Besides the high mortality, severe CBF reduction with marked infarctions may not adequately represent SIVD. In the current study, we tested ACs in SHRs and established the SHR-2VGO model which may more precisely mimic SIVD because of the underlying small vessel pathology.…”
Section: Introductionmentioning
confidence: 99%